Integration of EM Bokashi, Balanced NPK, Nanoparticles of Silicon and Selenium in Sustainable Soil and Physiology of Cabbage - Khalaf, Montather Hussein; Al-Juthery, Hayyawi W. A. (Research in Ecology, 2025)
A field experiment was conducted in the Al-Husseiniya region, Babylon Province, Iraq, during the autumn season to assess the environmental and agronomic impact of integrated fertilization strategies on hybrid cabbage (Brassica oleracea L., cv. Top White F1). The study evaluated the effects of soil application of effective microorganism (EM) Bokashi (5 Mg ha⁻¹), balanced NPK (Nitrogen, Phosphorus, and Potassium) (20:20:20 at 300 kg ha⁻¹), and foliar spraying with silicon and selenium nanoparticles (15 mg L⁻¹ each), applied in various combinations. The treatments aimed to enhance plant nutrition, promote sustainable soil fertility, and reduce reliance on synthetic inputs. A total of 16 treatments, including a control, were arranged in a randomized complete block design with three replications. Results revealed that the integrated application of EM Bokashi, NPK, Nano-silicon (SiNPs), and Nano-selenium (SeNPs) significantly improved the physiological and nutritional performance of cabbage. The highest concentrations of macro- and micronutrients, as well as essential amino acids, were recorded under this combined treatment. Notably, nitrogen (1.98%), potassium (3.11%), and micronutrients such as iron (185.6 mg kg⁻¹) and selenium (0.102 mg kg⁻¹) were substantially enhanced. Amino acid profiling via HPLC also indicated significant increases in key amino acids like methionine (28.42 mg/100 mg DW) and arginine (42.99 mg/100 mg DW). These findings suggest that integrating organic and nano-based fertilization approaches can improve crop nutritional quality while supporting environmentally sustainable agricultural practices.